2014
DOI: 10.1371/journal.pone.0101008
|View full text |Cite
|
Sign up to set email alerts
|

Partial Resistance of Carrot to Alternaria dauci Correlates with In Vitro Cultured Carrot Cell Resistance to Fungal Exudates

Abstract: Although different mechanisms have been proposed in the recent years, plant pathogen partial resistance is still poorly understood. Components of the chemical warfare, including the production of plant defense compounds and plant resistance to pathogen-produced toxins, are likely to play a role. Toxins are indeed recognized as important determinants of pathogenicity in necrotrophic fungi. Partial resistance based on quantitative resistance loci and linked to a pathogen-produced toxin has never been fully descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…Toxins were also found to be heavily involved in specific partial resistance in the Corynespora cassiicola /rubber tree pathosystem ( Barthe et al, 2007 ). More recently, toxin resistance was found to be correlated with QDR in several pathosystems, including the Stemphylium solani /garlic pathosystem ( Zheng et al, 2010 ) and, in our laboratory, the Alternaria dauci / Daucus carota pathosystem ( Lecomte et al, 2014 ).…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Toxins were also found to be heavily involved in specific partial resistance in the Corynespora cassiicola /rubber tree pathosystem ( Barthe et al, 2007 ). More recently, toxin resistance was found to be correlated with QDR in several pathosystems, including the Stemphylium solani /garlic pathosystem ( Zheng et al, 2010 ) and, in our laboratory, the Alternaria dauci / Daucus carota pathosystem ( Lecomte et al, 2014 ).…”
Section: Introductionmentioning
confidence: 73%
“…Potato dextrose broth ( Atlas, 2010 ) was used unless otherwise specified. Carrot juice medium ( Lecomte et al, 2014 ) was used in some specified cases. Liquid medium was inoculated with either conidial suspension to reach a final concentration of 5 ⋅ 10 3 conidia.mL -1 or 10 colonized agar plugs of 5 mm dia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 identified differences in genetic backgrounds between H1, I2 and K3. Numerous additional data suggested different resistance mechanisms between Boléro, I2 and K3 against A. dauci : induction of PR4, a gene from the jasmonic acid pathway, in K3 but not in I2 after A. dauci inoculation 42 , I2 being more resistant to fungal extract than Boléro and K3 43 , complementary favorable alleles for different rQTLs in I2 or K3 21 . From these previous results, we hypothesize that Boléro, I2 and K3 hosted different resistant mechanisms against A. dauci that could originate from differences in their secondary metabolite profile.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on phytotoxin production by A. dauci have reported the identification of some non-host-selective phytotoxins (non-HST′s), including alternariol, alternariol monomethyl ether, and zinniol [ 5 , 7 , 8 , 9 , 10 , 11 ]. Recently, it was demonstrated that zinniol is not responsible for the phytotoxic effect caused by the organic extract of A. dauci [ 12 ]; these results, which strongly suggested that the phytotoxic effect of the organic extract of cultures from A. dauci was caused by other lipophilic metabolites, were confirmed with the identification of aldaulactone as a new phytotoxin involved in the aggressiveness of A. dauci against carrot cells [ 5 ]. Given these findings, and as part of our continuing interest in the isolation and identification of phytotoxic metabolites produced by A. dauci and their role in the infection process, we wish to report here on the bioassay-guided purification and identification of α -acetylorcinol ( 1 ) and p -hydroxybenzoic acid ( 2 ) as two additional lipophilic phytotoxic metabolites produced by the fungal pathogen.…”
Section: Introductionmentioning
confidence: 96%